Presentation of sales price reserves for live lamb - Cehla, Béla (Acta Agraria Debreceniensis, 2009)
Although sheep breeding in Hungary is grounded in strong traditions, its activities only comprise 1% of the total production value generated from agriculture, and 2% of that for animal-based products. The most significant portion of incomes earned in the Hungarian sheep sector has, for years now, stemmed from the sale of live animals. The sector is decidedly export-oriented, as the domestic demand for its main product, i.e. lamb meat, and is minimal, equaling some 20-30dkg per person per year. Part of the sold animals is sold to market as dairy sheep, while the greater part is sold in the category of lamb carcasses. For this reason, the average weight of slaughter sheep has lied between 19-22 kg for years now. The target markets for live lamb sales are predominately Italy and Greece. In Greece, movement on this market has shown an upward tendency in recent years; noteworthy are also sales to Austria, Holland, Bosnia-Herzegovina and Poland. In 2003, we exported sheep meat in the form of carcasses to Italy, as well as to Germany, and of these exports, 94% went to Italy, while the remaining 6% went to Germany. Among sheep products, only the trade balance for live animal sales is positive. But even for such producers, only those who are specialized in intensive breeding and those sheep farms “targeting” meat production can obtain earnings. Specialized literature on the sector argues that the quality of Hungarian lamb has diminished dramatically and is beginning to lose its market position. If Hungarian lamb does not meet market expectations, then it will only be bought from producers at lower prices. My research focuses on those factors which influence price. I separately discuss the question of quality, as one of the most important decisive factors on price. Within this discussion, I describe the market expectations which actually have an effect on the acceptance of live animals for sale on commission. In practice, after the problems of quality, the next most important question is that of when sale is made. In the course of my research, I studied the development of averages for sales on commission of live lambs using statistical methods. The most important problem of this sector is the hierarchical system used in sales: this is the topic hich neither the producer, nor the buyer, wish to discuss, not even with each other. On the basis of the information at my disposal, I outlined the levels of traders and individual levels used to arrive at commission prices. Finally, I examined the components of the production value of live lamb sales. The results I obtained quantified the key role of the prices and the yield, as well as the factors influencing income.